Aberrant brain language network in schizophrenia spectrum disorder: a systematic review of its relation to language signs beyond symptoms - Alonso-Sanchez, María F.; Z-Rivera, Lucía; Otero, Mónica; Portal, Jorge; Cavieres, Álvaro; Alfaro-Faccio, Pedro (Frontiers in Psychiatry, 2024)
Background: Language disturbances are a core feature of schizophrenia, often studied as formal thought disorder. The neurobiology of language in SZ has been addressed within the same framework, that language and thought are equivalents. The aim of this review was to conduct a 1 systematic review of published peer-reviewed studies that employed neuroimaging techniques to investigate aberrant brain-language networks in individuals with SZ, in relation to linguistic signs.Methods: We employed a language model for automatic data extraction. Our study selection was made following the PRISMA recommendations, and the quality assessment of the selected studies was conducted according to the STROBE guidance.Results: We analyzed the findings from 37 studies, categorizing them based on patient characteristics, brain measures, and language task types. Among these studies and paradigms, the inferior frontal gyrus (IFG) and superior temporal gyrus (STG) exhibited the most significant differences.Conclusions: Based on our analysis, we propose guidelines for future research in this field. It is crucial to investigate larger networks involved in language processing, and there is a need to integrate language models with brain metrics to enhance our understanding of the relationship between language and brain abnormalities in SZ.